Synthesis and characterization of orotic acid loaded chitosan inclusion complex - Hassani, Abdelkader; Azad, Abul Kalam; Mia, Abdur Rashid; Helal Uddin, A.B.M. (2019)
Background: Polymeric inclusion complex has been used frequently as a drug delivery system due to controlled release, non-toxic properties and high bioavailability. Objective: The current study aims to improve drug release properties of orotic acid loaded with chitosan inclusion complex (OA/CS). Material and methods: The OA/CS inclusion complex were synthesized using freeze drying technique. The characterization of inclusion OA/CS was carried out using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffractometry (XRD), Differential Scanning Calorimetry (DSC), Zeta sizer, and Transmission Electron Microscopy (TEM). Results: The FTIR peaks of orotic acid have almost vanished in the OA/CS spectrum due to the restriction of OA vibration upon loading in CS cavity. The diffraction peaks of the OA/CS are completely diffused due to the amorphous state and the lack of crystallinity of inclusion complex. The DSC marked changes are indicative of the amorphous phase of solid dispersion, as well OA encapsulation into the nanocavity of CS. The size of OA/CS ranged between 58 nm and 200 nm and the zeta potential was 30 mV. In addition, transmission electron microscopy (TEM) showed that OA/CS sizes were ranged from 20 to 45 nm. Conclusion: Thus, this study indicates that OA/CS has promising future to further develop a carrier for drug delivery systems.